Enablers and restraints of knowledge work – Implications by certain professions? - Jussi Okkonen; Vilma Vuori; Nina Helander (Cogent Business & Management, 2018)
Knowledge work (KW) has risen to a significant role in modern societies, leading to an increasing number of the knowledge workers. Digitalization changes the work life, challenging individuals representing different professions as well as organizations. KW and the traditional professions are changing in many ways, opening up new vistas. The purpose of this article is to analyse and compare the enablers and restraints of KW in different professions: the medical practice, the clergy, the legal profession and the teachers. The article seeks the KW enablers and restraints similar or different between these selected professions, and further, discusses the impact of the identified enablers and restraints to work performance. The empirical data was gathered with unstructured interviews using a narrative interview method. Questions were open so that the situations were similar to a discussion. The interviewer posed further questions to deeper the interviewee's answers and to build the continuity of the interview upon them. This methodology puts in evidence on similarity of working habits, socio-technical systems and work-flows of within and between professions. The article also builds profession related taxonomy of key findings and discusses those from the performance and managerial perspective.
Keywords: 650